Comparison Between the Bees Algorithm and Genetic Algorithm Model in Manpower Allocation on Cell Loading Problem - AlMahasneh, Hossam Sayel (2010)
A number of resolutions to the cell loading problem have been stated in the literature. However, Manpower Allocation and Cell Loading (MACL) problem is comparatively new. Therefore, this thesis concentration on such topics. This research not only analyzes the MACL problem with a mathematical model and genetic algorithm (GA) and the Bees Algorithm but also it make a comparison among the mathematical models to measure the efficiency of the stated algorithm in solving the number of tardy jobs concept and also adds original aspects, the Cell Formation, the traditional GA methods. The objective of this thesis is to compare between GA and the Bees Algorithm on the MACL problem by both mathematical models and then compare the results in some cases. Results show that there are different factors of GA that it is not exist in the Bees Algorithm. Both of the proposed algorithm finds optimal or near optimal solutions for the MACL especially in large problems.